794 Learning by game playing and using digital media: an example through management of chemical exposure. (24th April 2018) - Mathieu, Laurence; Bigaignon, Janine; blomet, Joel; Gerard, Max
Abstract : Objectives: Chemical burn is relatively rare, frightening and potentially invalidating. Simple and effective means are necessary to become actors and not spectators before and during an accident. Methods: We started by designing a movie describing a chemical burn and explaining good practical guidance for management in hospital environment. After evaluation, we decided to target all occupational and safety professionals: a workshop took place during a congress introducing the gaming and fun notion of learning together. After assessing this workshop, we decided to move forward and improve contents and interactivity by elaborating a symposium workshop with the aim of including all occupational health and safety professionals and workers. Players commented the different steps and choices regarding their management. Time was given for evaluation followed by exchanges between all. Results: Over hundred professionals participated. They totally adhered to the project and were fully implicated. Confronted to real life situations, panic was observed as the most important point, patient pain and screams were heard but not cared for. The burn was not treated either immediately and unfortunately washing within the first minute was not observed. Various exchanges taking place following players' comments were rich and constructive and lessons were learnt. Conclusion: Our pedagogic tool performed relatively well but needed to be improve taking into consideration players remarks, our own observations as teachers as well as our final objective. Thus, a new film was created so that the concept be accessible to all OSH professionals and workers.